Iatrogenic injuries of the popliteus tendon during total knee arthroplasty. Issue 6 (30th June 2021) - Ammar, Ameni; Abcha, Oussama; Daghfous, Mohamed Samir
Introduction: The popliteus tendon is known to play a key role in the stability of the posterolateral corner of the knee. Its role in the stability of the replaced knee remains contentious. Objectives: The aim of this study was to determine the impact of an iatrogenic lesion of the popliteus tendon during total knee arthroplasty surgery on the stability and function of the knee Methods: We searched in the operating report registers, patients with complete iatrogenic injury of the popliteus tendon during total knee arthroplasty on genu-varum. We evaluated postoperative varus, mobility and stability and we calculated their International Knee Society scores Results: Among the 423 reports of total knee arthroplasties consulted in the operating report registers, we found seven patients with a complete iatrogenic injury of the popliteus tendon. All patients had preoperative extension deficit. All operated knees were stiff, tight and small. At postoperative follow-up, all the knees had good stability and function. All the patients were satisfied. Conclusion: we concluded that the isolated section of the popliteus tendon does not seem to modify the static stability of the knee. However, it can cause a decrease in long-term functional scores. More work is needed to increase understanding of the impact of this iatrogenic lesion on long-term function.